A atuação de uma gestora como uma das possibilitadoras da construção de uma escola pública com uma perspectiva democrática-emancipadora na Rede Estadual de São Paulo - Oliveira, Maria Aparecida Dias de (2012)
The present study has as its theme paths of democratic management in a public school in Basic Education state public network. The central focus of research is the role of managing the school as an enabler of building a school in a democratic-emancipatory perspective. The research is developed as a foundation with the trajectory of school management in order to understand personal and professional dimensions in the construction of identity management and intervention, as well as the process of self-training and their interfaces that contribute to their choices in school management. Resources are used for autobiography, and identity formation, in others words, the study was based on narratives of experiences that, in the contemporary scene, it is a qualitative methodology. The research has the timeline the period 2004 to 2011 and its objective, to resume the path traveled by management to evaluate the performance of school management with a focus centered on educational management with emphasis on curricular reorientation in a social and political context, experienced and constructed collectively, therefore, triggers demands for participatory management and school autonomy. This movement, at school, driving the need for continuing education within the school. The research shows, as a result of the trail traveled, teaching project management plan inserted in the school, as an object of research and analysis for relevance in curriculum development, participation and collective aspects of school autonomy